PENYELESAIAN KONFLIK ANTARA MASYARAKAT KENDENG UTARA DAN PT SEMEN INDONESIA DI KABUPATEN REMBANG - Dhanyra Nayla Talitha; Yulia Putri; Deni Angela (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2025)
The establishment of a cement factory by PT Semen Indonesia in the Kendeng Utara Mountains has triggered a prolonged conflict lasting 11 years due to local community resistance. Cement raw material mining activities are perceived as environmentally damaging, and the issuance of Central Java Governor's Decree No. 660.1/17 of 2012 on Environmental Permits is considered inconsistent with other regulations. This decision legitimized mining operations, exacerbating tensions between the community, environmental organizations, and the government. This study aims to identify the root causes of the conflict between the Kendeng community in Gunem District, Rembang Regency, and PT Semen Indonesia, while evaluating conflict resolution efforts. Using descriptive analysis based on literature reviews and digital media coverage, the study applies the theory of ecocentrism to examine the conflict dynamics. The findings reveal the presence of power dominance obstructing conflict resolution, despite various efforts by the community and non-governmental organizations. These results highlight the need for a more inclusive approach grounded in ecological justice to address the issue